2015
DOI: 10.1039/c5cp00838g
|View full text |Cite|
|
Sign up to set email alerts
|

New particle formation and growth from methanesulfonic acid, trimethylamine and water

Abstract: New particle formation from gas-to-particle conversion represents a dominant source of atmospheric particles and affects radiative forcing, climate and human health. The species involved in new particle formation and the underlying mechanisms remain uncertain. Although sulfuric acid is commonly recognized as driving new particle formation, increasing evidence suggests the involvement of other species. Here we study particle formation and growth from methanesulfonic acid, trimethylamine and water at reaction ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
3
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 80 publications
(152 reference statements)
7
110
3
2
Order By: Relevance
“…During periods when the CS entering the OFR in ambient air was larger, it reduced the condensation of SOA onto new particles, consistent with the lower importance of this mode for an OFR study in the Los Angeles area . These results support the possibility of using flow reactors to study the potential for new particle formation and growth in different ambient air masses and sources (Ezell et al, 2014;Chen et al, 2015).…”
Section: Condensation Vs Nucleation In the Ofrsupporting
confidence: 59%
“…During periods when the CS entering the OFR in ambient air was larger, it reduced the condensation of SOA onto new particles, consistent with the lower importance of this mode for an OFR study in the Los Angeles area . These results support the possibility of using flow reactors to study the potential for new particle formation and growth in different ambient air masses and sources (Ezell et al, 2014;Chen et al, 2015).…”
Section: Condensation Vs Nucleation In the Ofrsupporting
confidence: 59%
“…No amine particles were identified in the MSA query. As discussed earlier, the presence of MSA in TMA and other amine-containing particles is possible, as indicated by laboratory studies of particle formation and growth from reactions between MSA, TMA (or methylamine and DMA) and water (Chen et al, 2015a, b). Amines have been frequently observed in marine aerosol (Facchini et al, 2008;Gaston et al, 2010;Müller et al, 2009;Sorooshian et al, 2009), and particulate amine levels have been found to correlate with particulate MSA levels (Sorooshian et al, 2009).…”
Section: Msamentioning
confidence: 96%
“…However, closer inspection of individual spectra suggests that at least some of the signal at −95 arises from miscalibrated negative ion mass spectra, and is in fact associated with sulfate. Although m/z −95 cannot therefore be definitively assigned to MSA here, internal mixing of MSA and TMA is possible, as indicated by laboratory studies (Chen et al, 2015a, b). Furthermore, MSA was also measured in bulk PM 10 during this campaign using the PILS-IC instrument, and is thus inevitably contained in a fraction of particles at this location.…”
Section: Regionally Transported Combustionmentioning
confidence: 99%
“…Numerous lab experiments and quantum chemical calculations reported amines play an important role in atmospheric nucleation and the growth of new particles (Zhang et al, 2012;Jen et 5 al., 2014;Chen et al, 2015aChen et al, , b, 2017Olenius et al, 2017), and oxalic acid, one of the most abundant dicarboxylic acids, was also proposed to be involved in NPF, and to be more readily bound to methylamine than to ammonia (Guo et al, 2016;Arquero et al, 2017;Hong et al, 2018). So far, it has been a challenge to accurately measure the mass concentrations of aminiums and oxalate in nucleation mode particles (Bzdek et al, 2013;Tao et al, 2016).…”
Section: The Roles Of Amines and Oxalic Acid In Growing New Particlesmentioning
confidence: 99%